GANGGUAN PADA GARDU DISTRIBUSI TIPE PORTAL - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2016)
Means the latest in low voltage distribution systems for the provision of electric power supply before it gets to the customer, which generally are household customers. For medium voltage electric power system, the direct distribution system by using medium voltage 20 kV to substations - distribution substations then poured into PHB - TR and through the low voltage network forwarded kepelanggan. Medium voltage networks frequent disruptions. The cause - the cause disturbances in the portal substations and low voltage distribution systems. This research will discuss the disorder - disruption in the distribution on the type of portal. With a determines a disturbance more quickly, it can minimize the occurrence of a power outage.